The Future of Sex Robots in Indonesia: Law, Science, And Technology - Taqwa, Muhamad Dzadit; Alfarizy, Ahmad; Lasmaida Sirait, Melinda Yunita (Magister of Law, Faculty of Law, University of Mataram, 2023)
Sex robots are humanoid machines used to fulfill sexual desires of their users. Their presence has created debates around the world. Currently, sex robots are not sold freely in Indonesia. Although, the future of such an innovation has to be scrutinized through the Indonesian laws. From the proponent side, the existence of such robots has possibly several justifications: (1) their usage has no implications on other people other than their users; (2) the market is potentially high; and (3) the use of this object entails some psychological benefits for those in need of them. Conversely, the opposing group will potentially argue that this technology is not in line with the religious values, decency, and even the laws in Indonesia. We did not find any journals that had discussed sex robots, especially through a law, science and technology approach, so there is still a research gap. This article scrutinized sex robots through the law, science, and technology perspective in the context of Indonesia in order to bring up their impacts that may require legal involvement. In principle, the use of sex robots that are used individually does not mean that they cannot be prohibited, especially if they are against the law, violate moral values, and/or disrupt the public interests in Indonesia.